Effect of the welding parameters on microstructure and mechanical properties of linear friction welded Ti-6Al-4V alloy. (March 2022) - Choi, Jeong-Won; Aoki, Yasuhiro; Ushioda, Kohsaku; Fujii, Hidetoshi
Abstract: Linear friction welding (LFW) of Ti-6Al-4V alloy at various applied pressures and frequencies was performed. The influence of the applied pressure and frequency on the interfacial microstructure and mechanical properties of the joint was systematically investigated. The peak interfacial temperature was dominated by the applied pressure, while there is no significant variation in the peak interfacial temperature by the frequency. At low applied pressure, α-lamella structure formed inside the recrystallized β-grains since the interfacial temperature exceeded the β-phase transformation temperature. With the increasing frequency, the α-lamella spacing decreased due to the higher cooling rate. Furthermore, the dynamically recrystallized (DRX) β-grain diameter decreased because of the higher strain rate. At high applied pressure, the α-equiaxed grains formed since the interfacial temperature was lower than the β-phase transformation temperature. The grain diameter decreased as the frequency increased since both the strain rate and cooling rate increased. The higher applied pressure and frequency resulted in the higher Vickers hardness at the interfacial region due to the refined recrystallized grains. On the other hand, the tensile property indicated the equivalent tensile strength with the superior elongation, regardless of the processing parameters since there is no softening region in the obtained joints. An impact test revealed that the absorbed energy in the joint obtained at low applied pressure is higher than that obtained at high applied pressure, due to the fact that the lamella structure has a longer crack propagation than the equiaxed grain. Graphical abstract: Unlabelled Image Highlights: The relationship between interfacial temperature and applied pressure is inversely proportional. The interface temperature is not affected by the frequency. Both the heating and cooling rates increase with the increasing applied pressure and frequency. The grain diameter in weld center decreases as the applied pressure and frequency increase which leads to the increase in the hardness value.